ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS DAN RASIO PROFITABILITAS PADA PT SEMEN INDONESIA (PERSERO) TBK - Sartika, Yeyen; Puji Muniarty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the financial performance of PT Semen Indonesia (Persero) Tbk based on liquidity and profitability ratios during the period 2015–2024. This research was conducted to determine the company’s ability to meet short-term obligations and generate profits under fluctuating economic conditions. The method used in this study is a descriptive method with a quantitative approach. The data used are secondary data obtained from the company’s annual financial statements through documentation and literature study. The data analysis technique used is descriptive analysis through financial ratios, including Current Ratio (CR) and Quick Ratio (QR) for liquidity, as well as Return on Assets (ROA) and Return on Equity (ROE) for profitability. The results show that the company’s liquidity condition, as measured by CR, is generally in a good category because it is above the standard, although it fluctuates over time. However, the QR indicates that in several periods the company’s ability to meet short-term obligations without relying on inventory is still less optimal. Meanwhile, profitability ratios (ROA and ROE) show a declining trend during the observation period, indicating a decrease in the company’s effectiveness in generating profits from its assets and equity.